THE PSYCHOSOCIAL REHABILITATION OF MENTAL PATIENS IN REPUBLICAN VILNIUS PSYCHIATRIC HOSPITAL - Buginytė, Alma; Mickienė, Fausta (Socialinė teorija, empirija, politika ir praktika, 2007)
In recent years greater attention was given to the problem solution of mental patients, their rehabilitation, treatment and integration into community. Psychosocial rehabilitational measures need to be undertaken right away after the acute stage of an disorder, and carried on as long as necessary. They are indispensible for returning mentally disabled individuals into society and improving quality of their life. This paper conveys the result of statistical analysis of rehabilitational procedures performed by the social work department in Republican Vilnius Psychiatric Hospital (666 beds). The research was carried on adult patients with various disorders each year by means of questionnaires about involvement in rehabilitation activities at hospital and in the community. Their impact on the quality of life and evaluation of social workers’ pa1ticipation. l00 questionnaires were collected each year (2005 and 2006) and processed quantitively. Conclusions and recommendations for improvement of rehabilitative opportunities were formulated. While in hospital, the patients willingly joined occupational activities and viewed positively the assistance from social workers. However, the use of rehabilitational resources in the community decreased.
Keywords: Mental patients; Psychosocial rehabilitation; Survey; Republican Vilnius Psychiatric Hospital